2022
DOI: 10.12913/22998624/142962
|View full text |Cite
|
Sign up to set email alerts
|

Surface Topography of Inconel 718 Alloy in Finishing WEDM

Abstract: The properties of Iconel 718 determine its application for parts operating in extremely tough conditions. The diffi culties when machining nickel-based superalloys allowed in recent years for researching other machining methods. One of the proposed methods is Wire Electrical Discharge Machining (WEDM). It becomes possible to minimize or eliminate such problems associated with electrical discharge machining as microcracks, forming of a white layer, or high surface roughness. One way to avoid these issues is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…WEDM is particularly suitable for processing complex profile products made from heat-resistant nickel alloys, providing both accuracy and surface quality. The material removal from the craters depends on various EDM process parameters, including discharge current (I, A), discharge voltage (U, V), pulse duration (Ton), pulse off time (Toff), workpiece material, and electrode tool material [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…WEDM is particularly suitable for processing complex profile products made from heat-resistant nickel alloys, providing both accuracy and surface quality. The material removal from the craters depends on various EDM process parameters, including discharge current (I, A), discharge voltage (U, V), pulse duration (Ton), pulse off time (Toff), workpiece material, and electrode tool material [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to using basic surface roughness parameters, which are well-known and widely used, surface quality can also be evaluated based on the Abbott-Firestone curve and parameters describing this curve. The use of these parameters is a different approach to surface texture evaluation, one that can effectively be employed to evaluate the quality of surfaces obtained by different machining methods [33] to [35]. Material ratio curves were used, for instance, in the paper [36].…”
Section: Introductionmentioning
confidence: 99%
“…In the production of micro parts, the properties of the surface topography will have even more influence on the fatigue strength. Research conducted so far on WEDM of the Inconel 718 alloy [ 43 , 44 , 45 ] has shown that many factors have an influence on the surface roughness and the material removal rate. Relatively few studies [ 46 , 47 , 48 ] have described the influence of the parameters of micro-WEDM on the surface topography’s properties.…”
Section: Introductionmentioning
confidence: 99%